Experiências das mulheres-mães de pessoas com deficiência: da (in)visibilidade à participação social - Soares , Alessandra Miranda Mendes (2018)
This doctoral thesis, based on critical approaches to feminist and disability movements within the area of Cultural Studies, focuses on the empowerment of mothers of people with disabilities.The bibliographic survey on gender and empowerment of mothers of people with disabilities revealed an insufficient amount of research on the subject in Brazil and, consequently, the social invisibility of this group. An empirical study, based on grounded theory,aimed at assessing the contributions of Pro-Mothers Extension Project (Projeto de Extensão Pró-Mães) in the lives of participants – twenty women-mothers of people with disabilities. The project was designed for this thesis’s research purposes and carried out throughout the year 2015. The goal was to offer a formative process in order to catalyze the development of empowerment processes to counteract the adversities experienced by these women in different social contexts, allowing for the resignification of their experiences as women-mothers of people with disabilities, and for the exercise of empowerment both for their own benefit and for their children. A participant research was carried out based on the following guiding questions: What are the contributions of the Pro-Mothers Extension Project in the participants' lives? In what ways have their lives changed with their participation in the extension project? These questions intertwine with the emerging axes of analysis of the collected data, as suggested by grounded theory, namely, gender relations and care, maternal identity and child with disability, learning and empowerment. Research findings indicate that: (a) systematic encounters with mothers of people with disabilities were critical for them to learn new concepts and perspectives, to share common experiences, to feel welcomed in the group, to build their individual and collective identities; (b) arelationship was evident between the strengthening of their female-mother identity and their empowerment to solve issues in day-today life, as well as to act collectively in political and social spaces, in order to promote and defend their rights as mothers and the rights of their children. This experience was relevant in that it showed that those mothers could move from isolation to social participation whenever they had opportunitiesto access knowledge. Lastly, the project made it clear that it is very important for women-mothers to take ownership of information and disseminate it, thus benefiting other women-mothers of people with disabilities. Hence the need for studies on the subject and the creation and implementation of programs to enable the visibility and participation of this social group. In this regard, this thesis describes and analyses the implementation of such a program, which is, in turn, its main contribution.